The Exciton Absorption Spectrum of KPbI3 Thin Films - Yunakova, O. N.; Miloslavsky, V. K.; Kovalenko, E. N. (ФТИ им. А.Ф. Иоффе, 2014)
The absorption spectrum of KPbI3 thin films is studied in the spectral range 2–6 eV within the temperature interval 90–470 K. Localization of excitons in the sublattice of the compound containing lead ions is established. Excitons are shown to be of two dimensional nature.
Keywords: thin films; absorption spectra; exitons